Concentração de leveduras da fermentação alcoólica em hidrociclones - Bicalho, Isabele Cristina (2011)
In the fermentation process for ethanol production, the yeast Saccharomyces cerevisiae are recovered and recycled to a new stage of fermentation. This separation process is a major challenge, because the yeasts are small and low density. For this purpose the hydrocyclone emerges as an interesting alternative, because it uses the same principle of centrifugal separation, requires low maintenance and can be readily sterilized. This study aimed to optimize the separation process of yeast fermentation using hydrocyclones. To this end, was evaluated through experimental studies the influence of geometric and operational variables on the performance of hydrocyclones. A factorial experimental design (34) was applied and the results were used for the determination of empirical mathematical models that describe the capacity, total efficiency of separation, the flow ratio and reduced separation efficiency as a function of different geometric variables (feed inlet diameter, overflow diameter and angle of the hydrocyclone cone) and pressure drop. The geometry "optimum" founded was used in another factorial experimental design which aimed at evaluating the effect of concentration and pressure drop on the performance of the hydrocyclone. The diameters of the feed and overflow pipes studied were 2, 3 and 4 mm, while the angles of the hydrocyclone cone ranged from 6, 8 and 10º. The tests were conducted with suspensions of yeast in water with yeast concentrations from 0.5% to 5.5% by mass. All tests were performed at three different pressure drops (15, 23 and 31 psi). For yeast concentration of 1% was obtained total efficiencies of separation between 36.54 to 92.02%, reduced separation efficiencies from 4.67 to 55.59%, capacities from 0.1183 to 0.4579 m3/h and flow ratios, ranging from 31.74 to 84.30%. It also investigated the centrifugal forces generated within these devices ranging from 291g to 4153g. Analysis and discussion of the results show that the reduction of geometric variables with the increase in pressure drop and use of less concentrated suspensions led, in general, to an increase in total efficiency of separation. For the largest pressure drop conditions, the reduction of viability was checked and presented values below 6.76%. CFD techniques have also been applied in order to simulate the internal flow of a hydrocyclone.